Perbandingan Makna Hutang (Dain) dalam Al-Quran: Analisis makna Dain dalam Tafsir Ibnu Katsir dan Tafsir al-Misbah - Moh. Supriyadi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The rapid development of the era has given rise to new problems that need to be solved. The Qur'an as a holy book throughout the ages can certainly provide solutions to every problem, especially those related to debt, but a comprehensive and precise interpretation is needed for every problem that exists. The purpose of this study is to discuss the meaning of